Challenges and prospects of endosperm balance number in potato (Solanum tuberosum) improvement - GOPAL, JAI (The Indian Journal of Agricultural Sciences, 2014)
Endosperm Balance Number (EBN) is a genome-specific ploidy, which is not necessarily equivalent to the chromosome ploidy. The EBN is the ‘effective ploidy’ that determines crossability in Solanum species. It varies from 1 to 4 and the two Solanum species are crossable if they have the same EBN so that maternal to paternal ratio of EBN in the endosperm is 2:1. However, a number of significant exceptions to this rule have been observed in potato (Solanum tuberosum L.). EBNs have been experimentally assigned to a number of Solanum species after crosses with standard species whose EBN was arbitrarily established. Neither specific genes nor the molecular basis of EBN have been established in potato, but 2-3 unlinked loci with equal additive effects are known to determine the EBN in Solanum species. EBN acts as a powerful isolating mechanism in the sexual reproduction of Solanum species. EBN incompatibility played an important role in the speciation of polyploids from diploids, complementing the role of 2n gametes in the polyploidy evolution of potato species. EBN has great predictive value for planning interpsecific crosses in potato. EBN of a species can be modified through sexual or somatic polyploidization. This has facilitated the transfer of useful disease and pest resistance genes from 1 EBN and 2EBN wild species to 4EBN cultivated potatoes. Besides direct, indirect gene transfer through bridge species from otherwise incompatible Solanum species has been accomplished for improving cultivated potatoes. The concept, inheritance and role of EBN in speciation, and its prospects in potato varietal improvement are reviewed in this paper. The problems associated in transfer of useful traits from wild species to cultivated potatoes due to EBN barriers are also highlighted.